THE STUDENTS’ VOCABULARY ACQUISITION ADDICTED TO PLAYING ONLINE GAMES - Novia Alfitri; Arifmiboy Arifmiboy; Merry Prima Dewi (Universitas Mahaputra Muhammad Yamin, 2021)
This research aims to know students’ vocabulary acquisition influenced by playing online games. It wants to see the comparison of students’ vocabulary acquisition and the causes of similarities or differences in students who are addicted to playing online games with students who are not addicted. This type of research was causal-comparative by using mix method. The data were obtained through questionnaires, test, and interview. The population of this research of 117 students. To determine the sample, researchers used non-probability sampling, namely quota sampling. 73 students are addicted and not addicted. To analyze the data collected, researchers used the U-test by Mann Whitney using the SPSS 20 application with a significance of α = 0.05. With the provision of significance values> 0.05, accepted and is rejected, in this case, the researcher finds sig. (0.607> 0.05), it can be concluded that there are similarities between students who are addicted to not addicted. The occurrence of this equation is quite reasonable. Researchers used a questionnaire to group students who were addicted to playing online games. Then, a test was given to find out the comparison of students' vocabulary acquisition. After that, the data were analyzed using a U-test by Mann-Whitney. From the findings, it showed that there were similarities in students’ vocabulary acquisition between students who are addicted to playing games with students not addicted to playing games.